(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article analyzes the factors of further development and economic efficiency of the system of providing the population of our country with food, including fruits and vegetables, based on improving the organizational and economic mechanism of the horticulture system.